Estructura factorial de la Brief Self-Control Scale en español (2021)
The purpose of this study was to explore the factor structutre of the Brief Self-Control Scale (BSCS; Tangney, Baumeister y Boone, 2004) used as self-report with a sample of 151 children in Colombia (mean age 8.2 years, 50.33% girls and 49.66% boys) and 115 children in Chile (mean age 7.3 years, 53.04% girls and 49.95% boys). The scale was also answered by 80 of the Colombian children’s mothers (mean age 38.3 years) and the 115 mothers of the Chilean children (mean age 35.8 years) to evaluate their children’s self-control. The Exploratory Factor Analysis (EFA) revealed a bidimensional structure in all samples and acceptable internal consistency values. However, the composition of the factors  Overall findings are discussed in terms of cultural differences in self-control socialization practices and the development of self-regulation during the initial primary school years. According to these findings, self-control assessment using the BSCS in this age group requires.adjustments.differed notably between countries and between mothers and children.